Ontology for ethical issues in social networking site based on Ibn Khaldun’s thoughts - Mohamed Najid, Mohamad Hafizuddin; Zulkifli, Zahidah; Othman, Roslina; Rokis, Rohaiza (Faculty of Computing Universiti Malaysia Pahang, 2019)
Ontology is a hierarchically structured set of terms for describing a domain that can be used as a skeletal foundation for a knowledge base. Hence, we develop an ontology of ethical issues related to social networking sites (SNS) specifically on Twitter based on Ibn Khaldun’s thoughts. This project is aimed to identify the ethical issues from tweets related to Ibn Khaldun’s thoughts, develop the ontology, validate and verify the semantic relationship. The thoughts from Ibn Khaldun was identified from The Muqaddimah book and the protégé software will be used in building the ontology. This is expected that the outcome will give an understanding of the structure and help to design the ontology development of ethical issues in Twitter related to Ibn Khaldun’s thoughts.